Towards a transactive energy system for integration of distributed energy resources: Home energy management, distributed optimal power flow, and peer-to-peer energy trading. (October 2020) - Guerrero, Jaysson; Gebbran, Daniel; Mhanna, Sleiman; Chapman, Archie C.; Verbič, Gregor
Abstract: This paper reviews approaches for facilitating the integration of small-scale distributed energy resources (DER) into low- and medium-voltage networks, in the context of the emerging transactive energy (TE) concept. We focus on three general categories: (i) uncoordinated approaches that only consider energy management of an individual user; (ii) coordinated approaches that orchestrate the response of several users by casting the energy management problem as an optimization problem; and (iii) peer-to-peer energy trading that aims to better utilize the DER by establishing decentralized energy markets. A second separate, but important, consideration is that DER integration methods can be implemented with diverse levels of network awareness, given their capability to address system or consumer interests. This paper systematically classifies the existing literature on DER integration approaches according to these categories. In doing so, a review of the methods in each category is presented, and differences between the categories are identified and explained through a comparative analysis. In addition, case studies examine technical implementation considerations but leave market aspects aside. The analysis contained in this paper gives researchers and practitioners in DER integration the information needed to select a tailored approach to their specific power network and system integration problems. Highlights: We reviewed DER integration approaches towards a transactive energy system. We identified key elements to integrate behind-the-meter DER into power systems. Uncoordinated, coordinated and peer-to-peer approaches are formulated and compared. Technical implications of adopting exemplar DER integration methods are assessed. With high DER penetration, it is needed to explicitly consider network constraints.